The Health Disparities Field Experience: College students and community health workers in the field - Ernesto A Moralez; Beti Thompson; Kaitlin Englund; Marilyn Drennan; Nicole Mandall; Helena Loest (Wolters Kluwer Medknow Publications, 2020)
CONTEXT: Immersing students studying health promotion and disease prevention into community settings facing health disparities is an essential supplement to their academic experience. As part of many public health professions, these students will likely need to understand the values and beliefs of different cultures so that decisions of appropriate health promotion and treatment can be made equitably. This paper evaluates an education immersion program that was part of a National Cancer Institute funded collaboration supporting the recruitment and training of university students in cancer research. The primary aim of the Health Disparities Field Experience (HDFE) was to facilitate an experience for students pursuing a health-related degree to understand the conceptual issues in border/rural health and the cultural contexts related to health disparities among medically and financially indigent populations in the region. SUBJECTS AND METHODS: This study was conducted using qualitative research methods using a variation of the content analysis approach using open codes to categorize the data. Six students were selected to participate in the HDFE (five graduate students and one undergraduate) and all six of the participants completed pre- and post-test surveys. RESULTS: From the analysis of the data, posttest qualitative responses indicated that three participants saw racism as a primary cause of cancer-related disparities, a change from their pretest responses. When asked about the personal impact of the HDFE, respondents mentioned the importance of the experiential component. CONCLUSIONS: Participants learned about health disparities from the HDFE and expressed high satisfaction with this approach to education.